Fractalkine-upregulated milk-fat globule EGF factor-8 protein in cultured rat microglia - Leonardi-Essmann, Fernando; Emig, Michael; Kitamura, Yoshihisa; Spanagel, Rainer; Gebicke-Härter, Peter J. (Journal of neuroimmunology, 2005)
Fractalkine is the only known member of the CX3C-chemokine family, and so is its receptor CX3CR1. Fractalkine, typically is expressed by neurons where it is inserted in the plasma membrane (“chemokine on a stalk”). It can, however, be clipped off by a specific enzyme and diffuse into the extracellular space. CX3CR1 is primarily expressed by microglia, the phagocytes of the brain. This study was aimed at studying gene expression changes in cultured rat microglia upon fractalkine stimulation using gene chip technology. Six genes turned out to be upregulated, amongst which milk-fat globule EGF factor-8 protein (MFG-E8) was the most surprising, but also the most revealing one. We hypothesize that it serves as a bridging molecule between apoptotic cells (neurons) and microglia. Since the docking to microglia is, in part, mediated by members of the integrin family, six of these molecules have been-post hoc-included in real-time PCR confirmations of chip results. Two of them-integrin α2 and integrin β5-were upregulated as well. These data provide a much closer look into molecular mechanisms involved in apoptosis of neurons and their removal by microglia.
Gesehen am 03.11.2020